Engaging teaching strategies in neurology: the flipped classroom and simulation training. Issue 6 (21st July 2022) - Albin, Catherine; Berkowitz, Aaron L
Abstract : Just as neurology continues to expand its diagnostic and therapeutic modalities, so too does neurology education continue to expand in its pedagogical modalities. In this article, we describe two educational techniques—the flipped classroom and simulation—that we have incorporated in our teaching of neurology to students and doctors in training, with some practical tips for their successful implementation.